Revitalization of Malay Cultural Values in Regional Regulation of Spatial and Region in Medan City - Muhammad Yusrizal Adi Syahputra; Dani Sintara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The enactment of Regional Regulation of Medan City Number 13 of 2011 and Regional Regulation Number 2 of 2016 have not accommodated the importance of Cultural values in the process of formation on spatial and region planning so that the RTRW development carried out by the Medan City government is only based on regulation alone without looking further into the social context and culture. According to Von Savigny's Theory, the formation of law must be based on people's souls (Volkgeist) as the raw material for the formation of law. Therefore, in the formation of regional regulations must pay attention to the cultural values of the indigenous people of an area. The inclusion of Malay cultural values in regional regulations in Medan City is a form of the realization of the state implementing Article 18B paragraph (2) of the 1945 Constitution. Integration of the cultural values of the Malay people in Medan City into regional regulations is carried out through the implementation of the legislative functions of the Medan City Government and DPRD to accommodate and protect the soul of the nation from the original tribe of Medan City whose existence has been marginalized. Revitalizing the cultural value of the Deli Malay in Medan City into spatial and region regulation is a form of protection of the Medan city government towards the cultural, historical and social values of the Malay people in the Medan City.